Income Realization Concept for Sustaining Fish Balance: An Eco-Ethnomethodology of Fisherman Kawruh Jati - Whedy Prasetyo (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2024)
This qualitative eco-ethnomethodological research on kawruh jati fishermen aims to reveal the determination of fish balances. Balance sheet for determining fish potential with the reality of haul as a balance of fishermen's income. This reality creates real potential between haul and availability of fish. Therefore, the potential of fish haul using kawruh jati eco-ethnomethodology becomes an analysis tool. Data was collected through interviews and direct observation. The research results show that the reality of the haul is the main condition for income balance. Therefore, fish availability is the main value of fishing capacity that determines the amount of income realized in fishermen's exchange rate calculations. The realization of this exchange rate is based on the process of collecting one's income after sales. Conditions that make the preservation and continuity of marine resources or ecology a relationship that cannot be separated from intention or will. This situation means recording fish balances is realizing the fishermen's self-willed income and haul. This reality continues to bind or become necessary until that necessity is maintained as self-awareness for kawruh jati fishermen. This awareness means that fishing activities maximize fishing effort and availability of the fish itself. This realized balance can be used as a continuation of research to use an ethnographic approach based on participant observation as a complete source and an eliciting photography approach.